DESAIN JUMLAH TABUNG & SENSOR DALAM RANCANG BANGUN FIRE SUPPRESSION SYSTEM - Syahrial, ikbal; Abdurrahman, Tofan (MACHINERY Jurnal Teknologi Terapan, 2023)
The industrial sector is at high risk of fire hazards, so a system is needed to protect assets and workers. This research aimed to develop an effective system. The study used a method that utilized the effectiveness of an infrared sensor in a 300 square meter room. The sensor was placed 1 to 7 meters from the candle flame. The results showed that the room was highly effective if five sensors were installed, each at a radius of 4 meters, and two fire extinguishing system tubes were mounted on a 3-inch diameter pipe. The system's response time was still within the standard 10 seconds.